Exploring the intersection of settlement, subsistence and population in Manuā. - Quintus, Seth (Waka Kuaka, 2018)
The archaeology of Sāmoa has been structured around the investigation of settlement patterns and systems since the 1960s, and such investigations have been variously used to explore questions of temporal change relating to, among other things, political structure and subsistence. This same intellectual structure is applied here to the evaluation of variation between the geographically close islands of Ofu and Olosega, extending previous approaches by considering population estimates. These analyses, which include a calculation of carrying capacity and population estimates based on settlement patterns, suggest that Olosega supported a higher population density than Ofu, perhaps because of investments in tree cropping on the former. Variation in settlement distribution, subsistence strategies and population density has important implications for population resiliency and vulnerability in small-island societies.